Pengaruh Tata Kelola, Kinerja, dan Karakteristik Perusahaan terhadap Pengungkapan Modal Intelektual Perusahaan Properti dan Real Estate yang Terdaftar di BEI Periode Tahun 2012-2016 - Puspitarini, Prita Angelita; Panjaitan, Yunia (Universitas Multimedia Nusantara, 2018)
This study aims to analyze the influence of independent commissioner, profitability, leverage, company age, and company size to intellectual capital disclosure. The population in this research is property and real estate companies listed at Indonesia Stock Exchange (IDX) in 2012-2016. From 49 companies, there are 28 companies (140 observation data) which become the research sample. Data processing using Eviews 9. The result of the research shows that independent commissioner has significant effect on intellectual capital disclosure, profitability has no significant effect on intellectual capital disclosure, leverage has no significant effect on intellectual capital disclosure, firm age has significant effect on intellectual capital disclosure, and firm size has no significant effect on intellectual capital disclosure.Keywords- Independent Commissioner; Profitability; Leverage; Age Firm; Size Firm; Intellectual Capital Disclosure